PENGARUH TINGKAT SUKU BUNGA, PENDAPATAN, STATUS PEKERJAAN, JANGKA WAKTU KREDIT DAN TINGKAT PENDIDIKAN TERHADAP JUMLAH PENGAMBILAN KREDIT - Gerry Pranata Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2014)
The usefulness of this study (a) It is expected that the results of this study can be used as a discourse to consider the decision in the provision of credit to the customer, so as to increase the number of loan disbursements per year, and (b) The results of this study can be used as a reference to carry out further research as a source of information. The results obtained by analysis of: (1) Based on the results of the t test table can be seen in interest rates has a value of 781,714 and significance of 0,040. (2) Based on the results of the t test on the table it can be seen that the income of the customer has the value of 4.502 and significant 0,000. (3) Based on the results of the t test on the table it can be seen that the Job Status Customer has the value of 1.845.081 and significance of 0,373. (4) Based on the results of the t test on the table it can be seen that the credit period has a value of 539.831,2 and significant 0,000. (5) Based on the results of the t test on the table it can be seen that the level of education has a value B of 2.131.469 and a significance of 0,387. F test results obtained F value of 38,811 and sig = 0,000, meaning that the independent variable interest rates, customer income, employment status of the customer, the credit period, the level of education together or simultaneously significant effect on the dependent variable number of shots credit. The results obtained by calculating the coefficient of determination value of Adjusted R Square of 0,656. Keywords: interest rate, revenue, employment status, credit period, the level of education, taking credit amount.